Tax amnesty and taxpayers' noncompliant behaviour: evidence from Indonesia - Siti Nuryanah; Gunawan Gunawan (Cogent Business & Management, 2022)
This study aims to analyse tax noncompliant activities by specifically examining the effect of tax amnesty on taxpayers' compliant behaviour. Indonesia is taken as a case study since it is a populous country with a high dependency on tax revenue and a long history of tax reforms of more than 20~years. In this study, the 2008 tax amnesty is analysed since the policy targeted both individual and corporate taxpayers; hence it is argued to provide a more comprehensive analysis. The analysis is based on 5-year data before and after the 2008 tax amnesty (periods of 2003 to 2013). A trend analysis is conducted to show the compliance of both individual and corporate taxpayers in terms of the total number of taxpayers submitting annual tax returns and total income tax collected. In addition to the trend analysis, to examine the corporate taxpayers' compliance, this study conducts a regression analysis with a moderating variable of foreign investors to examine corporate taxpayers' compliance proxied by tax aggressiveness, before and after-tax amnesty. Manufacturing listed companies with a total of 783 observations are chosen as the sample. This study found that tax amnesty is effective in increasing the compliance of individual taxpayers only. The results show further that after-tax amnesty, corporate tax aggressiveness increased, and foreign investors are found to strengthen this condition.
Keywords: H25; H26; 650; book-tax difference; foreign ownership; Tax aggressiveness; tax reform